Magnesium: How Can We Benefit? - Habib, Syed Hamid (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Magnesium is one of the important minerals that has multiple physiological roles. However, its role has not been valued and has remained one of the most underestimated micronutrient imbalance. This is one of the reason for its low intake, and being ignored by physicians and nutritionists. Magnesium is mostly found in intracellular spaces of the body, mainly in skeleton complexed with calcium and phosphorus and also in soft tissues, muscles, and other organs.1 Magnesium is involved in a variety of biochemical and metabolic processes such as neuromuscular functions, bone deposition, energy storage etc. It also has role in the modification of intestinal microbiota and metabolism of different vitamins.